Social media and alternative discourse on natural hazard: a case study of Facebook group ‘Info Merapi’ - Nazaruddin, Muzayin (Penerbit Universiti Kebangsaan Malaysia, 2020)
Existing research on social media in disaster management usually focuses on the role of social media in emergency management, while the roles of social media in normal times are rarely examined. This study discusses the content of the Facebook group 'Info Merapi', which is dedicated to disaster risk reduction, especially in the context of Mount Merapi periodic eruptions. The materials of this research are the content of the group over two months periods during the normal times of Mt. Merapi volcanic activities, namely 10 July to 10 August 2016 and 20 August to 20 September 2019. The material was analysed with a critical discourse analysis approach. In addition, this study has also interviewed the admin of the group. This study concludes that in the disaster-prone areas social media have important roles in communicating risk and maintaining the preparedness of local people to future hazards. This study also concludes that Info Merapi represents the traditional beliefs of local people to live in harmony, both in harmony with nature and in harmony with the spirits of Merapi. The group also represents the discourse of 'beautiful Merapi', which is in sharp contrast to the discourse of 'dangerous Merapi' as commonly displayed by the Indonesian mainstream media. Info Merapi proposes the local peoples' perspective, focusing on the long normal periods, rather than emphasizing the short eruption periods. Finally, Info Merapi also shows the dominance of modern state-sponsored knowledge about Mt. Merapi and its eruption among local residents on the slopes of Mt. Merapi.